2016
DOI: 10.2118/180914-pa
|View full text |Cite
|
Sign up to set email alerts
|

Demulsifier in Injected Water for Improved Recovery of Crudes That Form Water/Oil Emulsions

Abstract: Waterflooding for oil displacement becomes a challenge when water-in-oil (W/O) emulsion forms upon contact of injected water with oil in the porous media. We have recently reported very-high pressure drops and high pressure fluctuations for a number of crudes in waterflooding. In this work, we address the challenge by adding a small amount of a demulsifier in the injected water. The stability of W/O emulsion is affected by many factors, including oil chemistry, brine chemistry, and temperature. We find that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…As the researchers highlighted, the excess pressure is required to initiate the flow due to the high mobility ratio as a result of the viscosity contrast. While finding an optimum demulsifier concentration, Sun et al also observed this pressure spike in cases where no demulsifier was added to the samples and emulsions were present. They concluded that the pressure spike and the following pressure fluctuations are minimized if an optimum concentration of demulsifier is added.…”
Section: Review On Parametric Sensitivity Analysismentioning
confidence: 95%
“…As the researchers highlighted, the excess pressure is required to initiate the flow due to the high mobility ratio as a result of the viscosity contrast. While finding an optimum demulsifier concentration, Sun et al also observed this pressure spike in cases where no demulsifier was added to the samples and emulsions were present. They concluded that the pressure spike and the following pressure fluctuations are minimized if an optimum concentration of demulsifier is added.…”
Section: Review On Parametric Sensitivity Analysismentioning
confidence: 95%
“…The spontaneous emulsification of oil and water has been related to (Abou-Kassem & Farouq Ali, 1986;Bennion, D. B., Bennion, D. W., Thomas, F. B., & Bietz, R. F., 1998;Chakravarty, Fosbøl & Thomsen, 2015;Cuthiell, D., Green, K., Chow, R., Kissel, G., & McCarthy, C., 1995;Kokal, 2005;Moradi, Alvarado & Huzurbazar, 2011;Pietrangeli, Quintero, Jones & Darugar, 2014;Rezaei and Firoozabadi, 2014;Sjöblom et al, 2003;Sun, Mogensen, Bennetzen & Firoozabadi, 2016;Wang and Alvarado, 2012):…”
Section: Summary Discussionmentioning
confidence: 99%
“…The combinations of surfactant/polymer and alkaline/surfactant/polymer have been considered to improve oil recovery, reduce the amount of surfactant use, and extend the range of effectiveness at high salt concentrations . As an alternative, low salinity water (LSW) injection in IOR has gained growing interest. When the low salt concentration is effective, it has been argued that the mechanisms may include wettability alteration, , reduction in IFT, clay migration, and more recently the increase of interfacial elasticity . The technique of adding functional molecules at ultra-low concentrations is highly sought-after for chemicals that are inexpensive, environmentally friendly, and effective at high salt concentrations. , Recently, we have shown that an ultra-low concentration of the demulsifier in the injection brine may improve oil recovery efficiency, which correlates to the increase in interfacial viscoelasticity .…”
Section: Introductionmentioning
confidence: 99%